Hydro-environmental changes assessment after Guadalhorce River mouth channelization. An example of hydromodification in southern Spain - Nieto-López, José Manuel; Barberá-Fornell, Juan Antonio; Andreo-Navarro, Bartolomé; Ramírez-González, José Miguel; Rendón Martos, Manuel (Elsevier, 2020)
The Guadalhorce River mouth (Málaga, Southern Spain) was channelized between 1997 and 2003 to reduce flooding potential in adjacent densely populated sections of Málaga. The channel was bifurcated near the Mediterranean Sea, surrounding an isolated wetland complex composed of eight different ponds. Groundwaterlevel and wetland-stage data, combined with water-chemistry data from wells and wetlands, collected since 1977, have documented the hydrological and ecological responses to channelization. The results show that channelization has extended the tidal influence inland from the Mediterranean Sea through the Guadalhorce River and the subjacent coastal aquifers, producing a change in groundwater hydrodynamics. The isolation of the wetlands resulting from channelization has provoked a significant salinization of both surface water and groundwater, the extent of which varies among wetlands. These decadal-scale changes in water chemistry have promoted the appearance or increase of halophilic vegetation and have caused a shift from diving birds to predominantly shorebirds in some wetlands. Documentation of these unexpected ecosystem responses is a necessary first step for land managers who need to consider groundwater and surface water as a single resource, particularly in groundwater-dependent ecosystems along the densely populated and ecologically sensitive Mediterranean coastal areas.
Keywords: Guadalhorce - Cauces; River hydromodification; Channelization works; Groundwater dependent ecosystems; Ecological impact; Guadalhorce river mouth